2019
DOI: 10.1177/0267659119859120
|View full text |Cite
|
Sign up to set email alerts
|

A skills acquisition study on ECMOjo: a screen-based simulator for extracorporeal membrane oxygenation

Abstract: Background: Extracorporeal membrane oxygenation relies heavily on didactic teaching, emphasizing on essential cognitive skills, but overlooking core behavioral skills such as leadership and communication. Therefore, simulation-based training has been adopted to instill clinical knowledge through immersive experiences. Despite simulation-based training’s effectiveness, training opportunities are lessened due to high costs. This is where screen-based simulators come into the scene as affordable and realistic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…From those, 25 publications indicated that the authors addressed human behaviors, communication and leadership skills, situational awareness and teamwork related to ECLS education and simulation training. 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Although much literature has emerged on identifying and optimizing human factors in high‐stress situations, little has been published on the specific ECLS‐related challenges. Guidance on the human factors influencing approach of creating ECLS teams, and managing these patients is lacking and mostly relies on individual institutional practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From those, 25 publications indicated that the authors addressed human behaviors, communication and leadership skills, situational awareness and teamwork related to ECLS education and simulation training. 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Although much literature has emerged on identifying and optimizing human factors in high‐stress situations, little has been published on the specific ECLS‐related challenges. Guidance on the human factors influencing approach of creating ECLS teams, and managing these patients is lacking and mostly relies on individual institutional practice.…”
Section: Methodsmentioning
confidence: 99%
“…The financial costs of simulation equipment limit their availability for ECLS training purposes 69,70 . Screen‐based simulators offer affordable and realistic alternatives 18 . The financial impact of simulator based ECLS education is currently unknown, complex to understand, and challenging to predict.…”
Section: Estimated Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skills are mastered without the involvement of the real patient; thus, patient safety is not compromised (11). Many forms of simulation can be used; from simple skill training models to full body mannequins for the clinical skills learning (12) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, used before mannequinbased training, computer simulations yield better learning and increase students' confidence (Curtin, Finn, Czosnowski, Whitman, & Cawley, 2011). Some computer simulators exist for training extracorporeal blood circulation, for instance ECMOjo (Alsalemi et al, 2020), but they focus on extracorporeal membrane oxygenation and not on CPB.…”
mentioning
confidence: 99%